A five-year experience of carbapenem resistance in Enterobacteriaceae causing neonatal septicaemia: predominance of NDM-1. - Saswati Datta; Subhasree Roy; Somdatta Chatterjee; Anindya Saha; Barsha Sen; Titir Pal; Tapas Som; Sulagna Basu (PLoS ONE, 2014)
Treatment of neonatal sepsis has become a challenge with the emergence of carbapenemase-producing bacteria. This study documents the trend of carbapenem susceptibility in Enterobacteriaceae that caused septicaemia in neonates over a five year period (2007-2011) and the molecular characterisation of Enterobacteriaceae resistant to carbapenems and cephalosporins. Hundred and five Enterobacteriaceae including Escherichia coli (n = 27), Klebsiella pneumoniae (n = 68) and Enterobacter spp. (n = 10) were isolated from blood of septicaemic neonates followed by antibiotic susceptibility tests, determination of MIC values, phenotypic and genotypic detection of β-lactamases. Carbapenem was the most active antimicrobial tested after tigecycline. CTX-M type was the most prevalent ESBL throughout the period (82%). New Delhi Metallo-β-lactamase-1 (NDM-1), which is a recent addition to the carbapenemase list, was the only carbapenemase identified in our setting. Fourteen percent of the isolates possessed blaNDM-1. Carbapenem non-susceptibility was first observed in 2007 and it was due to loss of Omp F/Ompk36 in combination with the presence of ESBLs/AmpCs. NDM-1 first emerged in E. coli during 2008; later in 2010, the resistance was detected in K. pneumoniae and E. cloacae isolates. NDM-1-producing isolates were resistant to other broad-spectrum antibiotics and possessed ESBLs, AmpCs, 16S-rRNA methylases, AAC(6')-Ib-cr, bleomycin resistant gene and class 1 integron. Pulsed field gel electrophoresis of the NDM-1-producing isolates indicated that the isolates were clonally diverse. The study also showed that there was a significantly higher incidence of sepsis caused by NDM-1-harbouring isolates in the male sex, in neonates with low birth weight and neonates born at an extramural centre. However, sepsis with NDM-1-harbouring isolates did not result in a higher mortality rate. The study is the first to review the carbapenem resistance patterns in neonatal sepsis over an extended period of time. The study highlights the persistence of ESBLs (CTX-Ms) and the emergence of NDM-1 in Enterobacteriaceae in the unit.